Video texture synthesis - Khaneja, Rishi. (2010)
This project investigates Video Textures, a type of video-based rendering technique, where new videos are synthesized from short sample videos that exhibit certain similarity or repetition in time. These textures are seamless and can be of any arbitrary length, and therefore give the illusion of being natural. Video textures, due to their small space requirement and dynamic qualities, can replace both still-photos and videos, especially in certain applications like display of dynamic scenes on web pages.